Pengaruh Kelas Ibu Hamil terhadap Pengetahuan tentang Kehamilan - Kasmiati Kasmiati (An-Najat, 2024)
The Pregnant Women Class is an activity to discuss the contents of the Maternal and Child Health (MCH) Handbook in the form of group face-to-face meetings, followed by discussions and experience-sharing between pregnant women and health workers. The goal is to improve the knowledge and skills of mothers regarding pregnancy, childbirth, postpartum care, postpartum family planning, prevention of complications, newborn care, and physical activities/exercises for pregnant women. The type of research used is an intervention study targeting pregnant women using a "pre-experimental" method with a "pretest-posttest with control group design." This design involves measurements in the pretest and posttest groups to observe the improvement in knowledge as a result of the intervention. The research was conducted in February 2022 at UPT Puskesmas Ulaweng, Ulaweng District, Bone Regency. The sample consisted of a subset of the population selected to represent it. In this study, the sample included pregnant women who participated in three Pregnant Women Classes held in February, totaling 40 participants. Correlation tests or relationship tests yielded a value of 0.373, indicating a moderate causal relationship between the increase in knowledge before and after attending the Pregnant Women Class. Meanwhile, the impact test showed a value of p=0.018 < α= 0.05, indicating that the Pregnant Women Class had a significant influence on knowledge about pregnancy at UPT Puskesmas Ulaweng, Ulaweng District, Bone Regency.